USING WINDOW NOTES STRATEGY TO IMPROVING STUDENTS’ READING SKILL IN NARRATIVE TEXT AT EIGHT GRADE OF MTS TAUFIQ WALHIDAYAH PEKANBARU - Dea Vrieska; Destina Kasriyati (ELT-Lectura, 2017)
At the eight grade of MTs Taufiq Walhidayah Pekanbaru, the researcher found some problem, such as the students at grade VIII.2 were not understand how to get main point of the text, they were not understand the meaning of word in Narrative text and they were difficult to differentiate between orientation and complication. They were not pass the passing grade (75), that was why the researcher conducted this research which aimed to improve students‟ reading skill in narrative text by using window notes strategy. This research was Classroom Action Research. There were 22 students involved as participants. The instruments used were test, observation, field note, and interview. This research consisted of two cycles in which each cycle consisted of four meetings and one test. After conducting this research, it was found that the students‟ ability in reading narrative text not improved in cycle 1. the average score was 71,36. Moreover, in cycle 2 the average score was 86,36 increase 15 points from cycle 1. The factor that influenced students‟ improvement of reading skill in narrative text by using Window Notes strategy at the eighth grade of MTs Taufiq Walhidayah Pekanbaru were Attention, Interesting and enjoyable. In conclusion, the use of window notes strategy is successfull to improve students‟ reading skill in narrative text at the eighth grade of MTs Taufiq Walhidayah Pekanbaru.